2000
DOI: 10.1063/1.1318728
|View full text |Cite
|
Sign up to set email alerts
|

Conductive layer near the GaN/sapphire interface and its effect on electron transport in unintentionally doped n-type GaN epilayers

Abstract: Temperature-dependent Hall effect measurements on unintentionally doped n-type GaN epilayers show that, above room temperature, the Hall-mobility values of different samples vary parallel with each other with temperature. We demonstrate that this anomaly is mainly due to a conductive layer near the GaN/sapphire interface for thin samples with low carrier density. Through trapping electrons, threading edge dislocations (TEDs) debilitate the epilayer contribution in a two-layer mixed conduction model involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…However, the interfacelayer effects become much weaker for the Si-doped GaN epilayers which have higher conductivity. It is reported that no interfacelayer effects are observed when the carrier density of epitaxial film is above ∼4 × 10 17 cm −3 [18]. In our case, the investigated samples A-F are all Si-doped and have higher carrier concentration than undoped GaN.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the interfacelayer effects become much weaker for the Si-doped GaN epilayers which have higher conductivity. It is reported that no interfacelayer effects are observed when the carrier density of epitaxial film is above ∼4 × 10 17 cm −3 [18]. In our case, the investigated samples A-F are all Si-doped and have higher carrier concentration than undoped GaN.…”
Section: Resultsmentioning
confidence: 73%
“…3, the carrier concentration of GaN samples decrease with the increase of growth time. The carrier concentrations are 9.1 × 10 17 , It has been reported that during the initial stage of GaN growth a thin interface layer is present near the sapphire interface, which may result in a conducting channel there [18]. It is expected that this may have an important effect on the Hall measurements, especially when the GaN films are thin enough.…”
Section: Resultsmentioning
confidence: 96%
“…[1][2][3][8][9][10] Some research groups reported that the conductivity is presumably due to doping by residual oxygen impurities. 3,9 Others reported that the dislocations in GaN are presumably electrically active.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the large lattice and thermal mismatch between GaN and sapphire, there is a highly defective layer near the GaN/ sapphire interface, which typically exhibits n-type conductivity. [1][2][3] It is still a challenge to control the resistivity of this interfacial layer in undoped GaN buffers grown on sapphire using the metal-organic chemical vapor deposition (MOCVD) technique. The properties of this interfacial layer and its influences on the material and device grown on it are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that when oxygen is incorporated in GaN layer, oxygen in N-site (O N ), a source of shallow donors with activation energy of 33.2 meV in GaN, is stable [22]. O N is difficult to be formed in other regions of the film away from the interface because of limited diffusion, resulting in the limited thickness of the high oxygen concentration, generating a highly conducting channel near the sapphire substrate [23].…”
Section: Resultsmentioning
confidence: 99%